2005
DOI: 10.1007/s10562-005-4885-3
|View full text |Cite
|
Sign up to set email alerts
|

Favorable synergetic effects between CuO and the reactive planes of ceria nanorods

Abstract: High-energy, more reactive {001} and {110} planes of CeO 2 nanorods were found to generate favorable synergetic effects between CuO and ceria, resulting in significant enhancement of the copper catalyst performance for CO oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 23 publications
0
35
0
1
Order By: Relevance
“…In this sense, further than the general specific surface area value, the interfacial area and/or its physicochemical characteristics appear to be most relevant to explain CO oxidation activity achieved by the catalysts. In the latter sense, changes in the type of interacting oxides surfaces appear also of relevancy, as reported in studies in which copper/ceria samples with different specific faces exposed in the CeO 2 component were prepared [52,53]. More doubts exist with respect to the selectivity (i.e.…”
Section: Co-prox Catalytic Activitymentioning
confidence: 82%
See 1 more Smart Citation
“…In this sense, further than the general specific surface area value, the interfacial area and/or its physicochemical characteristics appear to be most relevant to explain CO oxidation activity achieved by the catalysts. In the latter sense, changes in the type of interacting oxides surfaces appear also of relevancy, as reported in studies in which copper/ceria samples with different specific faces exposed in the CeO 2 component were prepared [52,53]. More doubts exist with respect to the selectivity (i.e.…”
Section: Co-prox Catalytic Activitymentioning
confidence: 82%
“…Concerning the former (CO oxidation), there is general consensus that it can be related to the presence of reduced states of copper (in the form of Cu + ) at copper oxide-ceria interfacial positions. The interfacial character of such sites basically determines that well dispersed CuO entities contribute most to the activity, although active interfaces could be obtained either in direct (CuO/CeO 2 ) or inverse (CeO 2 /CuO) configurations, the latter having large size CuO particles [52,53]. Such interfacial reduced states of copper could either be present in the initial catalyst [16] or (when starting with fully oxidized catalysts) are formed during the course of the reaction as a consequence of redox interaction with the reactant mixture [21].…”
Section: Co-prox Catalytic Activitymentioning
confidence: 99%
“…Through a deposition-precipitation method, CeO 2 nanorod-supported CuO catalysts were prepared. [66] It was found that CuO/CeO 2 -nanorods were more active for CO oxidation than the CuO/CeO 2 NPs. Temperature-programmed reduction (TPR) studies revealed a more favorable synergetic effect between CuO and ceria over CuO/CeO 2 nanorods compared with CuO/CeO 2 NPs.…”
Section: Supported Catalystsmentioning
confidence: 99%
“…Af ew studies were performed to elucidatet he synergistic effect between CuO and CeO 2 nanorods. [18] As the active sites (Cu, Cu + ,C u 2 + ,C uO x -CeO 2 )f or CO adsorption andc onversion in CuO x -CeO 2 still remain obscure, to further understand the CuO/Cu-CeO 2 interfacial effect, a comparative study was conducted on CeO 2 nanorod-supported CuO and reduced CeO 2 nanorod-supported CuO x catalysts for CO oxidation in this study.…”
Section: Introductionmentioning
confidence: 99%